Ion exchange involving calcium-potasium (Ca-K) and calcium-magnesium (Ca-Mg) in soil and organic matter fractions - Cofie, Olufunke O.; Pleysier, J. (2004)
The chemical characteristics of two soil types, an Alfisol and an Ultisol, were studied in the humid tropical zone of southern Nigeria. The objective was to investigate the contribution of soil organic matter (SOM) to nutrient retention characteristics and identify those SOM pools that contribute most to the ion exchange properties of the soils. Ion exchange studies involving K-Ca and Mg-Ca systems in whole soil, organic fraction (53-250 mm) and clay fraction (<2 mm ) showed a preference for Ca relative to K in the soil and organic fraction. For the clay fraction in Alfisol, the isotherm in K-Ca system suggested a preference for K at low K saturation, but from about 50% K saturation, the isotherm inferred a preference for Ca. However, the overall selectivity at constant temperature and pressure as expressed by Gibb's free energy change suggested a stronger binding of K than Ca by the fraction.